Effective passivation of HfO2/Ge interface by using nitrided germanate as passivation interlayer. Issue 6 (22nd March 2017) - Cheng, Zhi Xiang; Xu, Jing Ping; Liu, Lu; Huang, Yong; Lai, Pui To; Tang, Wing Man
Abstract : Ge metal‐oxide‐semiconductor (MOS) capacitor with YON/LaON, as interface passivation layer (IPL), and HfO2, as gate dielectric, is proposed to take advantage of both the good passivation effect by LaON and the suppressed intermixing between HfO2 and Ge by YON. As a result, superior interfacial and electrical properties are obtained, as compared to samples with only YON or LaON as IPL: high k value (19.5), low interface‐state density (6.64 × 10 11 cm −2 eV −1 ) and oxide‐charge density (−4.18 × 10 12 cm −2 ), small gate leakage current (1.15 × 10 −4 A cm −2 at V g = V fb + 1 V), and good high‐field reliability. Schematic diagram (a) and C – V curves (b) of the gate stack with YON/LaON dual IPL.